Implementation of Innovative Technologies in the Fields of Electronic Locks - Štefan Koprda; Martin Magdin (Universitas Ahmad Dahlan, 2016)
Almost every institution currently uses attendance system that ensures maintaining control over the attendance of employees, students and other persons. By using attendance system we can provide the right to enter certain rooms for only designated people. On the basis of reports from attendance system we can evaluate a monthly attendance of employees and the by that determine their real movement within the institution. Today is this system the usual standard in every medium and large institution, for example businesses, schools, universities and many others. The price for such a system, however, is often too high. Therefore companies opt also for other alternatives. Our task was to create a working prototype of such a system. Such a system must dispose at least with function for indicating the arrival and departure of employees to be able to determine the time of stay in the workplace. For this purpose we used the platform of microcontroller Arduino with a several basic sensors and software Arduino IDE. In this paper we present the achieved results in terms of applying different access cards.